Psychological manifestations of sexual abuse a cathartic autobiographic ritual - Cabatingan, Camille M.; Feleo, Roberto; Sta. Ana, Mary Catherine (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Psychological manifestations of sexual abuse trauma shouldn't be taken for granted as it may have long-term effects on the victim. The stigma associated with sexual abuse contributes to the repression of emotions and memories in the victim's psyche. The work aims to shed light on this topic through a ritual that gives visual form to sexual abuse trauma. The ritual employs sculpture, body painting and body movement improvisations in the framework of art therapy to give the performer of the ritual a cathartic experience. The process is the heart of the work as the artist confronts her sexual abuse trauma.
Appendix: leaves 29-34
Thesis (Bachelor of Fine Arts in Sculpture)
Bibliography: leaves 26-28
Keywords: Sexual abuse victims -- Philippines; Art therapy; Body painting; Catharsis